'From the Totem to the Antenna': Musique Concrète and the Universal at the end of the French Empire. Issue 4 (21st December 2020) - Ridout, Sam
Abstract: This article situates Pierre Schaeffer's musique concrète in the context of the end of the French empire. In drawing out conceptual continuities between Schaeffer's administration of colonial radio in the mid-1950s and works of musique concrète from the same period, I argue that both projects are predicated on a commitment to the capacity of acousmatic listening to provide access to universal essences. The invocation of the 'primitive' in Schaeffer's writing and music thus serves to buttress the universalizing rhetoric of musique concrète, portraying it as a neutral site for the reconciliation of different cultures, underwritten by a shared human essence. As such, musique concrète partakes in the logic of a colonial humanism, in which empire is conceived of as another such neutral framework. By way of conclusion, a form of acousmatic listening opposed to essence and empire is elaborated from the writings of Schaeffer's anticolonial contemporaries.